THE DETERMINANTS OF ACCEPTABILITY OF SOLAR POWER SYSTEMS: A SURVEY OF POWER CONSUMERS IN SOUTHERN SRI LANKA - Kodituwakku, T.P.; Dayaratna, D.A.I. (University of Colombo, 2015)
Currently majority of Sri Lankan population rely on grid connected electricity supply to fulfill their basic needs of energy. In view of reducing the electricity bill they limit their electricity consumption for several activities such as lighting, operating instruments etc. and usually they depend on wood fuel, L P Gas and other low quality fuels for cooking and other heating purposes. Such practices reduce quality of life and degrade the environment. As a solution for these problems, renewable energy sources like solar can be introduced as substitutes. Even though adequate solar resources are available in the country and the applications of solar technologies are feasible to use, power consumers have been reluctant to accept solar power systems to recover their day today needs yet. Solar Photovoltaic installations are at present becoming more financially attractive than earlier. It is now appropriate to make comprehensive evaluation of the acceptability of solar power. Promoting the development of economically viable new renewable energy sources are a key strategy under the national energy policy. The development framework of the government of Sri Lanka requires 20% of electricity generation from new renewable energies by 2020. An innovative environment of energy industry will encourage people to use new and renewable energy. Today solar power systems are becoming more popular in developed countries as well as developing countries. Understanding the present situations the solar power systems are developed with new technologies for affordable prices. 2 Therefore, this paper attempts to explore the determinants of public acceptance of solar power systems in Sri Lanka.
Keywords: THE DETERMINANTS OF ACCEPTABILITY OF SOLAR POWER SYSTEMS: A SURVEY OF POWER CONSUMERS IN SOUTHERN SRI LANKA